The relation between asymmetry and amplitude of the P300 field in schizophrenia - Hill, Holger; Weisbrod, Matthias (Clinical neurophysiology, 1999)
Objectives: A general reduction of auditory P300 amplitude is one of the most consistently replicated observations in schizophrenic patients. However, a left hemisphere amplitude reduction is discussed controversely. Methods: Encouraged by this controversy we analysed P300 data of 53 controls and 60 patients of the schizophrenia spectrum (ICD-10: F20, F23, F25). Results: Our main result was the finding of the correlation between general amplitude and hemispheric asymmetry in the patient group: low general amplitudes were assigned to a left hemispheric amplitude reduction, high amplitudes to a right hemispheric reduction. Based on this result, we grouped all subjects according to their hemispheric asymmetry pattern. The control group and the group of schizoaffective patients (F25) with a left hemispheric amplitude reduction showed the inverse asymmetry pattern of P300 amplitude compared to subjects with a right hemispheric amplitude reduction. In contrast, the schizophrenic patients (F20) showed only a difference in P300 amplitudes measured at electrode sites of the left hemisphere. Additionally, we could show, that the amount of the general amplitude reduction in patients was different between the diagnostic groups. Conclusions: We conclude that a left hemispheric amplitude reduction is not a general feature of schizophrenia but it seems to be pathological when combined with a general amplitude reduction.